Exploring the Future of Corpus Linguistics: Innovations in AI and Social Impact - Incelli, Ersilia (International Journal of Mass Communication, 2025)
This paper explores the evolving landscape of corpus linguistics, focusing on the impact of artificial intelligence (AI) and its social implications. Over the past two decades, the study of language through corpus linguistics has evolved significantly, prompting ongoing reflection on the field’s transformation. These reflections naturally give rise to pressing questions related to how corpus linguistics will evolve in a world defined by rapid technological progress and changing societal priorities. To validate the suppositions and reflections addressed in this contribution, the study explores a corpus that comprises scholarly papers from scientific journals, and a collection of AI-related articles taken from the media. This dual corpus enables a comparative analysis of how AI-driven corpus linguistics is represented, in order to explore how the integration of artificial intelligence is transforming corpus linguistics, and hence the methodological, theoretical, and socio-political implications of this shift. The methodological framework combines quantitative corpus analysis with qualitative discourse analysis. Collocation and keyword frequency retrieval is applied to identify prevalent themes. As expected academic literature emphasizes methodological advancements and data-driven rigor, while media discourse highlights ethical concerns and societal implications. These findings support the overview and contribute to understanding how AI is shaping both the practice and perception of corpus linguistics in contemporary society.